2007
DOI: 10.1007/s10722-007-9226-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Malus sieversii populations in Xinjiang, China

Abstract: Malus sieversii (Ledeb.) Roem. is a wild apple species which is distributed in the western mountains in Xinjiang, P.R. China, as well as in Central Asia, including Kazakhstan, Kyrgyzstan, Tajikistan, Uzbekistan and Turkmenistan. M. sieversii germplasm is valuable for plant breeders for drought, cold and disease resistance. Genetic polymorphisms of 20 populations of M. sieversii and 2 populations of M. niedzwetzkyana in Xinjiang, China were analyzed using RAPD markers. We present geographical distribution data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 12 publications
(10 reference statements)
1
30
0
Order By: Relevance
“…Moreover, the estimated F st value at two of the most significant SNPs (ss475879551 on LG9 and ss475881697 on LG16) was 0.12 and 0.09, respectively, so these SNPs were not outliers as per the observed F st distribution (Fig. The M. sieversii gene pool has shown significant resistance to apple scab and fire blight (Luby et al, 2002;Forsline and Aldwinckle, 2004) and may well hold genes that allow M. sieversii to adapt to cold and dry regions (Yan et al, 2008). A lack of strong marker-trait associations for most of the studied traits indicated that the SNP array used in this study comprised mainly neutral markers, so our inferences on admixture and population structure of Malus accessions would not be biased.…”
Section: Ld and Marker-trait Associationmentioning
confidence: 83%
“…Moreover, the estimated F st value at two of the most significant SNPs (ss475879551 on LG9 and ss475881697 on LG16) was 0.12 and 0.09, respectively, so these SNPs were not outliers as per the observed F st distribution (Fig. The M. sieversii gene pool has shown significant resistance to apple scab and fire blight (Luby et al, 2002;Forsline and Aldwinckle, 2004) and may well hold genes that allow M. sieversii to adapt to cold and dry regions (Yan et al, 2008). A lack of strong marker-trait associations for most of the studied traits indicated that the SNP array used in this study comprised mainly neutral markers, so our inferences on admixture and population structure of Malus accessions would not be biased.…”
Section: Ld and Marker-trait Associationmentioning
confidence: 83%
“…Malus sieversii has been considered an important germplasm resource for potential cultivar breeding of cultivated apples, making effective preservation of M. sieversii's genetic resources a major conservation target. Previous studies have identified priority conservation areas as areas displaying high levels of genetic diversity (Zhang et al 2007, Li et al 2008, Yan et al 2008, Zhang 2008. This approach has also been used to propose priority areas for conservation action on other endangered plants in the same region (Su et al 2, SRAP in Zhang 2008;3, SSR in Li et al 2008;4, SSR in Qin et al 2012;5, SSR in Dong et al 2013;6, LEAFY gene in Zhang et al 2015;7, SSR in the current study; 8, genome-wide SNPs in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of molecular marker data has been extremely useful for organizing and managing collections of genetic resources (Bretting and Widrlechner 1995;Van Treuren et al 2001). In particular, genetic analyses have been performed with microsatellite markers in cultivated and wild Malus collections for fingerprinting (Galli et al 2005;Guilford et al 1997;Hokanson et al 1998;Oraguzie et al 2005), genomic mapping (Hemmat et al 2003;Liebhard et al 2002;Liebhard et al 2003), marker-assisted breeding (Gianfranceschi et al 1999;Gygax et al 2004), and assessments of diversity within domesticated and wild collections (Coart et al 2003;Gaurino et al 2006;Hokanson et al 2001;Kitahara et al 2005;Lamboy et al 1996;Pereira-Lorenzo et al 2003;Ramos-Cabrer et al 2007;Volk et al 2005;Volk et al 2008;Yan et al 2008;Zhang et al 2007).…”
Section: Discussionmentioning
confidence: 99%